Skin autofluorescence is associated with inappropriate left ventricular mass and diastolic dysfunction in subjects at risk for cardiovascular disease - Wang, Chun-Cheng; Wang, Yao-Chang; Wang, Guei-Jane; Shen, Ming-Yi; Chang, Yen-Lin; Liou, Show-Yih; Chen, Hung-Chih; Lee, An-Sheng; Chang, Kuan-Cheng; Chen, Wei-Yu; Chang, Chiz-Tzung (Cardiovascular diabetology, 2017)
Background Enhanced advanced glycation end products deposition within myocardial tissue may cause diastolic dysfunction. However, whether this is related to left ventricular hypertrophy or inappropriate left ventricular mass remains unclear. Methods We prospectively enrolled 139 subjects at risk for cardiovascular diseases. We used echocardiography for measurements of left ventricular mass and cardiac systolic and diastolic functional parameters. An advanced glycation end product reader was applied for measurements of skin autofluorescence values. Comparisons of left ventricular mass and echocardiographic parameters between the higher and lower skin autofluorescence groups were analyzed. Results Compared with the lower skin autofluorescence group, left ventricular mass index and the ratio of observed left ventricular mass/predicted left ventricular mass (oLVM/pLVM) was significantly higher in the higher skin autofluorescence group (61.22 ± 17.76 vs. 47.72 ± 11.62, P < 0.01, 1.62 ± 0.38 vs. 1.21 ± 0.21, P < 0.01). After adjustment for potential confounding factors, skin autofluorescence was an independent factor for left ventricular mass index (β = 0.32, P < 0.01) and the ratio of oLVM/pLVM (β = 0.41, P < 0.01). Skin autofluorescence ≥2.35 arbitrary unit predicted left ventricular hypertrophy at a sensitivity of 58.8%, and a specificity of 73.0% (P < 0.01). Skin autofluorescence ≥2.25 arbitrary unit predicted inappropriate left ventricular mass at a sensitivity of 71.1%, and a specificity of 83.9% (P < 0.01). Skin autofluorescence was positively correlated with E/E′, an indicator for diastolic dysfunction (r = 0.21, P = 0.01). Conclusions Skin autofluorescence is a useful tool for detecting left ventricular hypertrophy, inappropriate left ventricular mass and diastolic dysfunction.